The role of e-government services on intention to use with mediator effect of citizens’ satisfaction in the UAE - Sabah Obaid, Qamar Mohamed (2022)
Intention to use E-Government services by citizens of United Arab Emirates (UAE) considered as vital element in the use of E-Government services. Previous studies were not focused on citizens’ intention to use E-Governmnet services hence, has highlighted the high need of the intention to use E-Government services and its indicators including service quality, system quality, information quality and cost to enhance the citizens’ intention to use E-Government services. The aim of this research is to empirically examine the citizens’ intention to use E-Government services in traffic police department in UAE. Moreover, this study identified the theoretical issues related to E-Government services and citizens intention to use E-Government with citizen’s satisfaction. The aim of the proposed conceptual framework is to determine the role of E-Government towards citizens’ intention to use, along with citizens satisfaction as mediator in UAE. In addition, the study utilizes citizen’s satisfaction as mediating variables in the effect of service quality, system quality, information quality and cost towards intention to use E-Government services. A well-structured questionnaire were used and also validates the proposed conceptual framework using a quantitative approach with the data collected from 380 respondents from the users of E-Government services of traffic police department. This study is carried out through an empirical review of literature and development of hypotheses therefore all of the hypothesis including mediator’s hypothesis of the formulated framework were proved to be positive and supported. The findings suggest that E-Government services including service quality, system quality, information quality and cost has a significant positive impact on intention to use E-Government services. This study finds that citizens’ satisfaction is a mediator between service quality, system quality, information quality and cost in order to enhance citizen’s intention to use E-Government services. This study will help UAE government to improve intention to use E-Government services; this influence can affect in the context of traffic police departments of the UAE. Further, researcher of this work attempts to develop a conceptual and empirically tested framework with service quality, system quality, information quality, and cost and citizens’ satisfaction as mediators.